Kinetic Studies for the Esterification Process with Ionic Resin Catalyst: Optimization using Response Surface Methodology - Kumar Sriramoju, Kishore; Mekala, Mallaiah; Gowrishetty, Srinivas; Chimmiri, Venkateswarlu (International Journal of Engineering and Technology, 2018)
The esterification reaction between acetic acid (AA) and methanol was studied in a batch reactor with solid catalyst. The temperature range applied was 323.15 K to 353.15 K. Experiments with feed mole ratios ranging from 1:1 to 1:4 were conducted. The influence of temperature, catalyst loading, initial reactant mole ratio, and the reaction time on AA conversion has been investigated. To design experiments, central composite method of response surface methodology (RSM) has been used for the esterification process.Â  A regression model is developed for AA conversion. The model correlates the acetic acid conversion and four significant independent variables. The four most significant variables are temperature, mole ratio of reactants, catalyst loading and reaction time. The statistical test shows that the model is well fitted with experimental data. It is observed from present investigation that model is predicting theÂ  experimental data at optimum conditions for acetic acid conversion.Â
Keywords: Esterification; Kinetics; Solid Ionic Resin Catalyst; Response Surface Method.